2007
DOI: 10.1080/01449290601173499
|View full text |Cite
|
Sign up to set email alerts
|

How older people account for their experiences with interactive technology

Abstract: We present a qualitative study, undertaken over a period of nine months, of older people facing the challenges of learning to use interactive technology, specifically personal computers (PCs) and the internet. We examine the range of causal explanations (attributions) voiced by the group in accounting for their difficulties with it. A discourse analysis of these data reveals some factors (anxiety, age-related issues, being too busy to learn and the need for a purpose for the new tools) that support the work of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 27 publications
5
66
1
3
Order By: Relevance
“…Results are in line with those of other researches [25], [26], [27]; [28], [29], and showed that negative stereotypes of people who are not digital natives as avoidant of technology and incapable of its use are outdated.…”
Section: A Qualitative Opinions On the Experiencesupporting
confidence: 80%
“…Results are in line with those of other researches [25], [26], [27]; [28], [29], and showed that negative stereotypes of people who are not digital natives as avoidant of technology and incapable of its use are outdated.…”
Section: A Qualitative Opinions On the Experiencesupporting
confidence: 80%
“…In particular when evaluating interactions between older adults and software, most of the efforts have been focused on product design to address the physical and cognitive aspects of aging. Ethnographic studies on the use of computing techniques by older adults suffering from Alzheimer's disease (Morris et al 2003), older adults' experiences with rehabilitation tools (Morán et al 2014), and mobile technologies in general (Lee 2007) as well as the problem of learned helplessness, which has been observed among older adults who interact with ICT devices (Turner et al 2007) are some of the examples of the experience-centered approach in application design.…”
Section: Participatory Designmentioning
confidence: 99%
“…Relatywnie najczęściej opinię taką formułują właśnie ludzie w wieku 50-64 lat 20 . Należy dodać, że pod koniec 2013 r. osoby z grupy wiekowej 50+ stanowiły ponad 24% ogółu zarejestrowanych bezrobotnych w porównaniu z 22,8% przed rokiem i niespełna 16% w 2005 r. Oznacza to, że na przestrzeni ostatnich ośmiu lat udział ten zwiększył się o ponad 8% 21 .…”
Section: Zachowania Dyskryminacyjne I Marginalizujące Starszych Wiekiunclassified